ANALYSIS OF COMPLICATIONS FOLLOWING UNICOMPARTMENTAL KNEE ARTHROPLASTY - Stanislav Karamitev; Stoyan Ivanov; Vihur Kovachev (Peytchinski Publishing, 2022)
Purpose: the aim of the present study is to evaluate the intra- and postoperative complications following unicondylar knee arthroplasty and subsequent outcome. Material and methods: For the period from 2008 to 2018, we operated on 450 patients with isolated osteoarthritis of the knee joint. In the majority of cases, patients had arthrosis of the medial compartment of the joint due to antero-medial osteoarthritis or osteonecrosis and, in smaller percentage, osteoarthritis in the lateral part of the joint. Results: Various complications were registered which we divided into intraoperative and postoperative, monitoring during the follow-up of patients. Intraoperative include fracture of the tibial plateau during implantation of the component, partial resection of the intercondylar eminence during the preparation of the tibial plateau, incorrect hole placement in the femoral condyle, which led to malalignment positioning of the femoral component in varus or valgus, resection of more bone substance from the tibia leading to subsidence of the implanted component. The postoperative complications include: aseptic loosening, polyethylene wear, impingement, progression of osteoarthritis in the opposite part of the knee joint, periprosthetic infection and arthrofibrosis. Conclusion: Unicompartmental knee arthroplasty is a minimally invasive procedure for the treatment of isolated osteoarthritis of the knee joint and is associated with excellent and good long-term results. Complications could be reduced by using a meticulous surgical technique, selection of suitable implants and last but not least proper indications for surgery.